Selam gazetesine göre Rodos Türkleri - Orakçı, Meryem (My University, 2011)
Rodos’un ilk Türkçe gazetesi olan Selam, Mayıs 1926’da İtalya hâkimiyeti döneminde Arap harfleriyle yayınlanmaya başlamış, 10 yıl kadar devam etmiştir. Gazete, Rodos Türklerinin iki dünya savaşı arasında yaşadıkları bocalama, tedirginlik ve yeni yönetime alışma sürecini canlı bir şekilde yansıtmaktadır; aynı zamanda, onların gündelik hayatları, diğer cemaatler ve İtalyan hükümetiyle ilişkileri hakkında önemli bilgiler vermektedir. Selam, İslam Cemaatinin yayın organı olmakla birlikte, Rodos Musevilerinin de gazetesi idi. Bu çalışmada, bugüne kadar hiç ele alınmamış bir gazete olan Selam gazetesi ve burada verilen bilgilerin ışığında Rodos Türkleri ele alındı. Bu çalışma sayesinde Rodos Türklerinin sosyal ve kültür hayatını tespit etmek mümkün oldu. Gazeteyi incelemek suretiyle, söz konusu 10 yıl içinde İslam Cemaatindeki değişiklikleri ve yenilikleri takip etme imkânına sahip olduk. İddia edildiğinin aksine, Rodos Türklerinin hiç de aşağı kesimi oluşturmadıkları, adadaki üretime etkin bir şekilde katıldıkları ve Rodos’un ileri gelenlerinin azımsanmayacak bir kısmını Türk eşrafının oluşturduğu tespit edilmiştir. Rodos Türklerinin diğer cemaatlere göre biraz geri olmakla birlikte, eğitim düzeyi bakımından da oldukça iyi durumda oldukları kanaati hasıl olmuştur. İslam Cemaati kurumunun bu durumu daha da iyileştirmek noktasına odaklandıkları gazetede yayınan yazılardan anlaşılmaktadır. Rodos Türkleri, Selam gazetesi, Rodos Musevileri, Hizkia Franko, Mehmed Kadri, Mario Lago

The first Turkish newspaper of Rhodes, Selam, began under the period of Italian rule in May 1926 in Arabic script and continued to be published for ten years. The newspaper gives lively information about the process of the Turkish population’s adaptation to the Italian rule and reflects their confusion and hesitations; at the same time, the newspaper informs us about Turks daily life, their relationships with Jewish and Greek population as well as their contact with the Italian government. Although, Selam was an organ of the Muslim Community, its chief editor and a considerable portion of its writers came from Jewish origin; therefore, the newspaper also reflected the situation, needs and wishes of the Jewish population of the island. This dissertation, for the first time, studied the Selam and concentrated especially on the Muslim Turkish population of the island under the light of information given in this newspaper. By studying the newspaper, this dissertation aims at illuminating the social, cultural and intellectual developments of the Turks of Rhodes during the ten years of Italian government. This study will goes on to search about the changes and developments within the period. Contrary to the claims that the Turks of Rhodes were consisted the lowest status of the island in terms of economical and intellectual situation, this study discovered that they consisted the considerable portion of the notables of the island and contributed a great deal to the production. The research also disclosed that although the Turks of Rhodes were somewhat slow in progress comparing with the Jews and Greeks, the members of the Muslim Community did their best to develop the schooling system; it is evident from the writings and decisions published at the newspaper. the Muslims or Turks of Rhodes, Selam newspaper, the Jews of Rhodes, Hizkia Franco, Mehmed Kadri, Mario Lago
Keywords: Gazeteler; Tarih_Türkler; Türkler_Basın